Meta-Analysis: Effectiveness of Scoliosis Brace to Reduce Scoliosis Curve Degree in Adolescent Idiopathic Scoliosis - Etanaulia Marsim; Hanung Prasetya; Bhisma Murti (Masters Program in Public Health, Sebelas Maret University, 2023)
Background: Adolescent Idiopathic Scoliosis (AIS) is a disorder of the spine that is curved laterally which includes rotation of the spine so that there is humpback on the ribs, which occurs in children aged 10-18 years. The use of a brace is an attempt to modify the mechanical shape and control the development of curves in the curvature of the spine by applying certain pressure points on the body. The purpose of this study was to determine the magnitude of the effect of using the scoliosis brace to reduce the degree of scoliosis in adolescents with idiopathic scoliosis.Subjects and Method: This study was conducted using a systematic review and meta-analysis study design using PICO, population: adolescent idiopathic scoliosis, intervention: using a scoliosis brace. comparison: not using a scoliosis brace, outcome: degree of scoliosis. The articles used in this study come from 3 databases, namely Google Scholar, PubMed, and Science Direct. With keywords including